Epidemiological evidence for a hereditary contribution to myasthenia gravis: a retrospective cohort study of patients from North America. Issue 9 (18th September 2020) - Green, Joshua D; Barohn, Richard J; Bartoccion, Emanuela; Benatar, Michael; Blackmore, Derrick; Chaudhry, Vinay; Chopra, Manisha; Corse, Andrea; Dimachkie, Mazen M; Evoli, Amelia; Florence, Julaine; Freimer, Miriam; et al.
Abstract : Objectives: To approximate the rate of familial myasthenia gravis and the coexistence of other autoimmune disorders in the patients and their families. Design: Retrospective cohort study. Setting: Clinics across North America. Participants: The study included 1032 patients diagnosed with acetylcholine receptor antibody (AChR)-positive myasthenia gravis. Methods: Phenotype information of 1032 patients diagnosed with AChR-positive myasthenia gravis was obtained from clinics at 14 centres across North America between January 2010 and January 2011. A critical review of the epidemiological literature on the familial rate of myasthenia gravis was also performed. Results: Among 1032 patients, 58 (5.6%) reported a family history of myasthenia gravis. A history of autoimmune diseases was present in 26.6% of patients and in 28.4% of their family members. Discussion: The familial rate of myasthenia gravis was higher than would be expected for a sporadic disease. Furthermore, a high proportion of patients had a personal or family history of autoimmune disease. Taken together, these findings suggest a genetic contribution to the pathogenesis of myasthenia gravis.